Disease monitoring of epidermal growth factor receptor (EGFR)‐mutated non‐small‐cell lung cancer patients treated with tyrosine kinase inhibitors via EGFR status in circulating tumor DNA. Issue 15 (1st July 2022) - Li, Yan; Xu, Ziyi; Wang, Shouzheng; Zhu, Yixiang; Ma, Di; Mu, Yuxin; Ying, Jianming; Li, Junling; Xing, Puyuan
Abstract: Objective: Circulating tumor DNA (ctDNA) monitoring proves to be a promising approach to assess response and predict survival in epidermal growth factor receptor ( EGFR )‐mutated non‐small‐cell lung cancer (NSCLC) patients treated with tyrosine kinase inhibitors (TKIs). However, whether the dynamic changes in ctDNA EGFR mutation status have the same predictive value as ctDNA remains unknown. This study aims to explore the predictive value of dynamic changes in both ctDNA and ctDNA EGFR status. Methods: A retrospective analysis was performed using 91 ctDNA samples from a cohort of 28 patients who were diagnosed with EGFR ‐mutated NSCLC and treated with EGFR ‐TKIs, including 14 patients treated with first‐/second‐generation TKIs and 14 treated with osimertinib. Blood samples at baseline (BL), within 4 weeks after TKI initiation (Week4), within 12 weeks before progression (pre‐PD), and at progression were collected. The relationship alternatives in ctDNA status, ctDNA EGFR status and response to EGFR ‐TKIs as well as progression‐free survival (PFS) were analyzed. Results: We categorized 20 BL‐ctDNA positive patients with available Week4‐ctDNA into two groups: ctDNA‐clearance ( N = 7, 35%) and ctDNA‐non‐clearance ( N = 13, 65%). The ctDNA‐clearance group had better PFS than the ctDNA‐non‐clearance group (ctDNA‐clearance vs. ctDNA‐non‐clearance, p = 0.091, hazard ratio [HR] = 0.42, 95% confidence interval [CI] = 0.15–1.19). According to Week4‐ EGFR status, we observed that PFS was significantly longer in EGFR ‐clearance patients than EGFR ‐non‐clearance groups, ( p = 0.011, HR = 0.23, 95% CI = 0.08–0.72). We then categorized patients into three subgroups according to Week4‐ctDNA and Week4‐ EGFR status: non‐clearance ( N = 9), only‐ EGFR ‐clearance (concomitant alterations non‐clearance) ( N = 4), and all‐clearance ( N = 7). The nonclearance group had a significantly worse PFS than the all‐clearance group (median PFS = 5.07 vs. 11.40 months, p = 0.029, HR = 3.45, 95% CI = 1.05–11.49). The only‐ EGFR ‐clearance group had a similar PFS to the all‐clearance group ( p = 0.607), which was longer than that of the non‐clearance group (median PFS = 9.20 vs. 5.07 months, p = 0.060, HR = 0.25, 95% CI = 0.05–1.18). We found that the all‐clearance group had a similar objective response rate (ORR) to the only‐ EGFR ‐clearance group ( p = 1.000) and a higher ORR than the non‐clearance group ( p = 0.012). Conclusion: Monitoring of EGFR clearance in ctDNA is promising and cost‐effective in assessing response and predicting survival in EGFR ‐mutated NSCLC patients treated with EGFR ‐TKIs, with similar predictive value to ctDNA surveillance. Abstract : This study analyzed the relationship alternatives in circulating tumor DNA (ctDNA) status, ctDNA epidermal growth factor receptor ( EGFR ) status, and response to EGFR ‐tyrosine kinase inhibitors (TKIs) as well as progression‐free survival (PFS). We observed that PFS was significantly longer in EGFR ‐clearance patients than EGFR ‐non‐clearance groups ( p = 0.011, hazard ratio [HR] = 0.23, 95% confidence interval [CI] = 0.08–0.72), and that the only‐ EGFR ‐clearance group had a similar PFS to the all‐clearance group ( p = 0.607), which was longer than that of the non‐clearance group (median PFS = 9.20 vs. 5.07 months, p = 0.060, HR = 0.25, 95% CI = 0.05–1.18). In conclusion, monitoring of EGFR clearance in ctDNA is promising and cost‐effective in assessing response and predicting survival in EGFR ‐mutated non‐small‐cell lung cancer patients treated with EGFR ‐TKIs, with similar predictive value to ctDNA surveillance.